2021
DOI: 10.2147/rmhp.s308039
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices of Medical Students Regarding COVID-19 in Afghanistan: A Cross-Sectional Study

Abstract: Background The coronavirus pandemic has had devastating effects on many nations, including Afghanistan. Public awareness and following recommendations play an important part in managing such a large-scale crisis, which are affected largely by knowledge, attitudes, and practices (KAP). Medical students can act as reliable sources of information for the public in such a scenario. This study aimed to investigate KAP of medical students regarding COVID-19. Methods A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
6
22
0
1
Order By: Relevance
“…A high level of adherence to COVID-19 preventive measures was also observed in studies that targeted medical students in developing countries like Jordan [20,21], Iraq [26], Iran [27], Pakistan [28], Afghanistan [29], KSA [30], and UAE [31]. All of these studies revealed highly prevalent good behavior regarding COVID-19 preventive measures among the studied students with very high healthy behaviors scores.…”
Section: Discussionsupporting
confidence: 72%
“…A high level of adherence to COVID-19 preventive measures was also observed in studies that targeted medical students in developing countries like Jordan [20,21], Iraq [26], Iran [27], Pakistan [28], Afghanistan [29], KSA [30], and UAE [31]. All of these studies revealed highly prevalent good behavior regarding COVID-19 preventive measures among the studied students with very high healthy behaviors scores.…”
Section: Discussionsupporting
confidence: 72%
“…In response to COVID-19, different countries in Southeast and South Asia were also raised an alert and implemented wide-ranging, multi-agency public health measures under WHO guidelines to fight against the pandemic. As COVID-19 appears to be transmitted from person to person, almost all countries in Southeast and South Asia initiated a public campaign highlighting the necessity of practicing respiratory hygiene, hand hygiene and using appropriate personal protective equipment (PPE) ( 1 , 23 , 28 , 29 , 43 , 44 , 47 , 49 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 These findings are also consistent with studies done on medical students in Jordan, India and Afghanistan. 5,11,12 This understanding about safe practices by medical students provides additional benefit to the society as it can reflect directly on the general public.…”
Section: Discussionmentioning
confidence: 99%